Pengaruh Dana Otonomi Khusus, Pengeluaran Perkapita, Umur Harapan Hidup Saat Lahir, Harapan Lama Sekolah, dan Rata-Rata Lama Sekolah Terhadap Indeks Pembangunan Manusia di Provinsi Papua Tahun 2014-2022 - Ryana Syafira; Rifki Khoirudin; Indanazulfa Qurrota A’yun (Universitas Nusantara PGRI Kediri, 2024)
During the period of 2014-2022, the province of Papua experienced a Human Development Index (HDI) level below the national average, and the rankings of HDI indicators also tended to be lower compared to other provinces. This research aims to explore the impact of HDI indicators on the HDI levels in various districts/cities in the province of Papua. The research approach used is a correlational method with a focus on understanding the correlation between dependent and independent variables. Regression analysis techniques were applied to the districts/cities in the province of Papua over the period of 2014-2022. The research findings reveal that the special autonomy fund indicator has a negative and non-significant effect on the Human Development Index in the province of Papua during that period. Meanwhile, the indicators of per capita expenditure, life expectancy at birth, expected years of schooling, and average years of schooling positively and significantly influence the improvement of the Human Development Index in the province of Papua during the same period.